Transient global amnesia in a collegiate baseball player with type I Diabetes Mellitus: a case report - Gravlee, J. R.; Barrett, J. J. (Journal of Athletic Training, 2011)
Objective: To present the case of a collegiate pitcher with type I diabetes mellitus who developed transient global amnesia and to characterize the acute onset of symptoms and clinical diagnosis of this rarely reported neurologic condition in the student-athlete population.